Mother to offspring transmission of chronic wasting disease in reeves' muntjac deer. - Amy V Nalls; Erin McNulty; Jenny Powers; Davis M Seelig; Clare Hoover; Nicholas J Haley; Jeanette Hayes-Klug; Kelly Anderson; Paula Stewart; Wilfred Goldmann; Edward A Hoover; Candace K Mathiason (PLoS ONE)
The horizontal transmission of prion diseases has been well characterized in bovine spongiform encephalopathy (BSE), chronic wasting disease (CWD) of deer and elk and scrapie of sheep, and has been regarded as the primary mode of transmission. Few studies have monitored the possibility of vertical transmission occurring within an infected mother during pregnancy. To study the potential for and pathway of vertical transmission of CWD in the native cervid species, we used a small cervid model-the polyestrous breeding, indoor maintainable, Reeves' muntjac deer-and determined that the susceptibility and pathogenesis of CWD in these deer reproduce that in native mule and white-tailed deer. Moreover, we demonstrate here that CWD prions are transmitted from doe to fawn. Maternal CWD infection also appears to result in lower percentage of live birth offspring. In addition, evolving evidence from protein misfolding cyclic amplification (PMCA) assays on fetal tissues suggest that covert prion infection occurs in utero. Overall, our findings demonstrate that transmission of prions from mother to offspring can occur, and may be underestimated for all prion diseases.